Evaluation of the disease burden of nosocomial infection among inpatients in a cancer hospital based on propensity score matching - Jiayang Tang; Jiang Yuan; Hui Wang; Qin Huang; Weiwei Yang; Qingqing Tian; Anran Liu; Hailin Zhang; Chunlin Wu (Frontiers in Public Health)
BackgroundOncology patients, as an immunocompromised population, are particularly susceptible to hospital-acquired infections (HAIs). This study aims to establish a scientifically sound model to estimate the disease burden associated with HAIs in oncology patients, providing valuable decision-making support for healthcare systems and public health management.MethodsPropensity score matching (PSM) was employed. Post-matching permutation tests were applied to compare hospitalization costs and lengths of stay between the HAIs and non-HAI groups, as well as between the multidrug-resistant bacteria (MDRO) infection group and non-MDRO group.ResultsThe results indicate that the average hospitalization cost in the HAIs group was 23.7% higher than the non-HAI groups, with a median difference of 12,417.6 CNY. Among various hospitalization expenses, the largest disparity was observed in the cost of Western medications, which had a median difference of 5,453.79 CNY, representing a 54.38% increase. The average length of hospital stay in the HAIs group was 1.33 times that of the control group. For the MDRO infection group, the average hospitalization cost exceeded that of the control group by 56.43%, with an absolute difference of 32,266.62 CNY. Additionally, the average length of hospital stay in the MDRO group was 42.11% longer, extending by 8 days.ConclusionBoth HAIs and MDRO infections significantly increase hospitalization duration and costs. The resulting disease burden is reflected in the direct escalation of health economic costs and the indirect effects of reduced hospital operational efficiency and heightened strain on the healthcare system. On this basis, we conclude that the funds for the prevention and control of HAIs and MDRO infections should be increased, and the measures for the prevention and control of HAIs should be implemented effectively, so as to reduce the direct and indirect economic burdens caused by HAIs and MDRO infections.